Preferences Prospective Students In Choosing The Study Program (University X In Bandar Lampung) - Indriati Agustina Gultom; Wahyu Pamungkas (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The existence of a material consideration or reference in taking decisions be important for management; where one of them is to bridge between supply manufacturers to match consumer demand. Many factors behind a prospective students in choosing courses be quite important for the management of the University in preparing the draft strategy right. Factors election so many courses that need to be grouped, in addition to ease, as well as to structuring elements such varied. AHP, or the Analytical Hierarchy Process Model is a model that can be used to provide structuring a good direction, so that the complexity of factors will become more structured and taken into consideration in the decision.